Real-time barcode reader using personal digital assistance (PDA) - Elsherairi, Osama Salem (2007)
This project concerns the design and implementation of a system for real time barcode reader using personal digital assistant (PDA) with built-in camera. A system that reads and decodes (1D) linear barcodes based on images containing barcodes – independent of the barcodes' orientation or rotation. Problems associated with images taken by the PDA are limited depth of field, limited resolution, poor lighting sensitively and camera shake. To accomplish this project with the above constraints the following stages are undertaken; First the image from the camera is enhanced, the camera will send continuous frame of images from the environment. These images are converted to grayscale and some preprocesses are performed, image is filtered (such as sharpening and noise reduction) and converted to binary. The image is then scanned horizontally, vertically and diagonally for barcodes, thus enabling it to detect rotated barcodes to suit the subsequent processing. Then the barcode is located in the image using a method based on the evaluation of the correlation. To extract relevant information from the located image the barcode is then isolated from the image, after that it is used to gain a waveform that represents the information of the barcode. Finally, the waveform will be wavered into a string of digits representing the widths of each bars of the barcode. At this stage the processing has completely decoded the barcode symbology. This project only considers European Article Number 13, (EAN-13) barcodes. The system has been implemented in Windows Mobile (windows CE) based software in Embedded Visual Studio 2005 C++ on PDA, with a graphical user interface. Error correction and predictive decoding is implemented to improve the capability accuracy and performance of the system.